Are Pedobarographic and Gait Analyses Useful Tools to Evaluate Outcomes of Anterograde Calcaneo-Stop Procedure in Pediatric Symptomatic Flexible Flatfoot? - Daniela Dibello; Valentina Di Carlo; Federica Pederiva (MDPI AG, 2022)
Background: Flexible flatfoot is a frequent condition in childhood that needs to be treated when symptomatic. The aim of this study was to analyze pedobarographic and gait outcomes of patients with painful flexible flatfoot who underwent the anterograde calcaneo-stop procedure. Methods: All patients scheduled for surgical correction of painful flexible flatfoot between April and September 2011 were offered to participate in a study of dynamic pedobarographic and gait analyses before surgery and 3, 12, and 24 months after surgery. A healthy control group of similar age and physical characteristics also underwent dynamic pedobarographic and gait analyses. Results: Fifteen patients accepted to undergo dynamic pedobarography and gait analyses. The data were compared with fifteen controls of similar age and BMI. No significant differences were found on dynamic pedobarography within patients at different endpoints, except for a decreased percentage of plantigrade phase and increased percentage of digitigrade phase at 12 months post-op in comparison with 3 months post-op, nor when compared with control. Similarly, when range of motion was taken into consideration, no significant differences were found within patients at different endpoints, nor when compared with control, except for a decrease in ankle joint range of motion 24 months post-op in comparison with the controls. The stride was significantly decreased before surgery and became like controls 24 months after the procedure. The cadence, significantly decreased 24 months after surgery in comparison with the pre-surgical set, was similar to the controls. No significant differences were seen in the walking speed within patients at different endpoints and the controls. The cycle time significantly increased 24 months after surgery when compared to the pre-op situation, and was similar to the controls. Conclusion: Dynamic pedobarographic and gait analyses were useful not only to identify the gait impairment in patients with symptomatic flexible flatfoot, but also to measure the treatment outcome through the analysis of the surgery's impact on the gait quality.